Soil test based fertilizer recommendation under IPNS for vegetable guar in Torripsamments of Rajasthan (Indian Journal of Arid Horticulture, 2013)
Soil test crop response correlation studies were conducted with vegetable guar under integrated plant nutrition  system (STCR-IPNS) in Torripsamments of Rajasthan during Kharif 2003. Fertilizer adjustment equations under IPNS  were formulated for vegetable guar following Ramamoorthy's inductive-cum targeted yield model. The nutrient  requirement for producing one quintal of veg. cluster bean was found to be 6.80, 1.17 and 4.62 kg of N,P O and K O, 2 5 2 respectively. The per cent nutrient utilization efficiencies from soil and fertilizer nutrients were found to be 72.72 and 59.62  for N, 33.93 and 17.73 for P O and 45.34 and 50.10 for K O, respectively. Like wise the percent nutrient utilization 2 5 2 efficiency from farmyard manure (FYM) was 200 for N, 32.66 for P O and 137.92 for K O, respectively. In STCR-IPNS 2 5 2 technology, the fertilizer doses are tailored to the requirements of specific yield targets of veg. cluster bean taking into  account the contribution from soil, fertilizers and organics.
Keywords: Vegetables cluster bean; STCR-IPNS; fertilizer adjustment equations; Torripsammennts